2021
DOI: 10.1097/apo.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Mobile Teleophthalmology for the Detection of Eye Disease in Minorities and Low Socioeconomics At-Risk Populations

Abstract: Purpose: To examine the benefits and feasibility of a mobile, real-time, community-based, teleophthalmology program for detecting eye diseases in the New York metro area. Design: Single site, nonrandomized, cross-sectional, teleophthalmologic study. Methods: Participants underwent a comprehensive evaluation in a Wi-Fi–equipped teleophthalmology mobile unit. The evaluation consisted of a basic anamnesis with a questionnaire form, brief systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Our study is not the first to utilize remote image analysis. A pilot study in northern Manhattan, New York demonstrated a high prevalence of undiagnosed ocular pathology; however, our study differs in that screening images were collected by medical students, and we incorporated an on-site ophthalmologist to validate the accuracy of the telehealth recommendations [20]. The Philadelphia Telemedicine Glaucoma Detection and Follow-Up Study utilized a primary care telehealth ophthalmologic screening, followed by eye examination for those who needed it [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is not the first to utilize remote image analysis. A pilot study in northern Manhattan, New York demonstrated a high prevalence of undiagnosed ocular pathology; however, our study differs in that screening images were collected by medical students, and we incorporated an on-site ophthalmologist to validate the accuracy of the telehealth recommendations [20]. The Philadelphia Telemedicine Glaucoma Detection and Follow-Up Study utilized a primary care telehealth ophthalmologic screening, followed by eye examination for those who needed it [21].…”
Section: Discussionmentioning
confidence: 99%
“…1 Preclusion of the use of important diagnostic tools reduced follow-up for disease monitoring, and a substantial reduction in the performance of glaucoma surgery occurred. 8 US counties with high-poverty indices were disproportionately influenced by less utilization of telehealth services. 1 Importantly, these studies also directly comment on an expected ophthalmologic challenge of delayed patient care secondary to the pandemic for ophthalmic diseases, including retinal disease and glaucoma.…”
mentioning
confidence: 99%
“…Specifically, Medicare Advantage beneficiaries residing in rural isolated, small rural, and large rural areas utilized telemedicine visits significantly less than beneficiaries residing in urban areas (adjusted incidence rate ratio: 0.822, 0.754, 0.711, all P < 0.05) 1 . Preclusion of the use of important diagnostic tools reduced follow-up for disease monitoring, and a substantial reduction in the performance of glaucoma surgery occurred 8 . US counties with high-poverty indices were disproportionately influenced by less utilization of telehealth services 1 .…”
mentioning
confidence: 99%
“…In addition, mobile health units are readily accessible, and some have already been launched in New York City (NYC), specifically real-time mobile teleophthalmology for the detection of eye disease in minorities and low socioeconomic at-risk populations. In this recent launch, 900 individuals were screened in high-risk communities in NYC between 2017 and 2018 and 48% were referred for ophthalmic evaluation 3…”
mentioning
confidence: 99%
“…In this recent launch, 900 individuals were screened in high-risk communities in NYC between 2017 and 2018 and 48% were referred for ophthalmic evaluation. 3 Another way of dealing with increasing disease burden is home monitoring, kiosks, or remote monitoring centers. The devices available for in-home monitoring are numerous, some of which are implantable, such as intraocular pressure sensors (eg, EyeMate device), and some rely on the operator, such as tonometers for intraocular pressure measurements at home, and virtual reality visual field devices.…”
mentioning
confidence: 99%